A model for the structure of chromatin in mammalian sperm (The Rockefeller University Press, 1982)
DNA in mammalian, and most vertebrate sperm, is packaged by protamines into a highly condensed, biochemically inert form of chromatin. A model is proposed for the structure of this DNA-protamine complex which describes the site and mode of protamine binding to DNA and postulates, for the first time, specific inter- and intraprotamine interactions essential for the organization of this highly specialized chromatin. In this model, the central polyarginine segment of protamine binds in the minor groove of DNA, crosslinking and neutralizing the phosphodiester backbone of DNA while the COOH- and NH2-terminal ends of protamine participate in the formation of inter- and intraprotamine hydrogen, hydrophobic, and disulfide bonds. Each protamine segment is of sufficient length to fill one turn of DNA, and adjacent protamines are locked in place around DNA by multiple disulfide bridges. Such an arrangement generates a neutral, insoluble chromatin complex, uses all protamine sulfhydryl groups for cross linking, conserves volume, and effectively renders the chromatin invulnerable to most external influences.